An Analytical Study of Morality in Cambodian Traditional Wedding at Chamnomkuet Village, Chamnom Sub-district, Mongkolborei District, Banteay Meanchey Province, Based on Buddhist Principle - Bhaddharakhito, Phra Channa (Dhammathas Academic Journal, 2015)
This research has three main objectives : 1) to study the concept of marriage in Buddhism, 2) to study morality in traditional wedding in Chamnomkuet village, Chamnom sub-district, Mongkolborei district, Banteay Meanchey province and 3) to analyze morality of Cambodian traditional wedding based on the Buddhist principle. This is a qualitative research, to collected data from documents and interviews of respondents in Chamnomkuet villagers and presented in a descriptive analysis. The results of this analytical study were found that all ceremonies in Cambodian wedding are being influenced by many religious teachings from both Buddhism and Hinduism. These influences established a philosophy of life based on the religious concepts but Buddhism has a power and plays a role to show a way of life, what is right or wrong, what should one do or not do, etc. Actually, Buddhism teaches a good householder who seeks happiness with mundane pleasure in the Tipitaka and some commentaries such as Garavasa Sutta, Bramavihara Dham, Mongkola Sutta, Anguttara Nikaya etc. Buddhism teaches moral conduct about security, responsibility, gratefulness, monogamy in order to serve as guidelines to encourage a successful married life. Cambodian people created their tradition in order to educate the younger generation to understand and encourage their life with right way leading to peace and happiness in their marriage. Chamnomkuet wedding morality manifest philosophy of life that depends upon the guidelines of gratefulness returning to parents, relatives, family, neighbors, even to spirits, ancestors, ghosts, angels and God. In addition, Cambodian traditional role educates people in order to lead a happy married life and sufficiency in daily life based on monogamy. Chamnomkuet wedding morality is similar to Buddhist principle, but the researcher has found that some ancient beliefs and some Hindu principles such as: worshipping or dedicating to spirits, ghosts, angels or God to beg the happiness without the moral conduct is not of any advantage and it does not encourage Cambodian society. Moreover, the foreign cultural influence has taught people to seek happiness with desire, especially materialism in the present life. It destroyed the moral conduct in the society. It brought the problems in the society. With ordinary people aimed at seeking pleasure and desires, Cambodian society gradually forgot the good morality. Thus, modern civilization with its focus on materialism and consumerism made people greedy about comfort-seeking and mundane happiness.